1998
DOI: 10.1111/j.1524-4725.1998.tb04062.x
|View full text |Cite
|
Sign up to set email alerts
|

Short-Pulse Carbon Dioxide Laser Resurfacing in the Treatment of Rhytides and Scars

Abstract: Histopathological studies suggest improvement of rhytides and scars by CO2 laser resurfacing may be attributed to new collagen formation following treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…As had been seen with dermabrasion, elevated scars responded better than depressed scars. Shim et al reported similar improvement of scars treated with carbon dioxide resurfacing lasers and showed an increase in collagen layer thickness histologically that was sustained for the one year follow up of the study [11]. In a split scar study, Nehal et.…”
Section: Discussionmentioning
confidence: 59%
“…As had been seen with dermabrasion, elevated scars responded better than depressed scars. Shim et al reported similar improvement of scars treated with carbon dioxide resurfacing lasers and showed an increase in collagen layer thickness histologically that was sustained for the one year follow up of the study [11]. In a split scar study, Nehal et.…”
Section: Discussionmentioning
confidence: 59%
“…Several reports confirm that new collagen synthesis after cutaneous resurfacing accounts for improvements of fine wrinkles on the face [1,2,5,11,12]. Given that the scanned laser works deeper in the dermis and affects a greater depth of new collagen synthesis, one might expect that the scanned laser would be more efficacious than the short-pulsed laser in removing deeper wrinkles.…”
Section: Discussionmentioning
confidence: 95%
“…While comparisons between the thermal damage depth created by the scanned and short-pulsed lasers has been done in human skin [5,11,12], we believe that our in vivo experiments with piglets have clinical relevance. Porcine skin has been shown to be very similar to human skin in such parameters as hair growth, thickness, and sweat glands [13,14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on currently available systems, some general observations can be made: CO 2 by using current techniques generally remove up to 220 m of tissue, leaving a residual zone of irreversible thermal necrosis of 50-100 m [9,24,25]. An additional zone of reversible thermal injury also remains, which represents the "repairable injury" zone that triggers wound remodeling and in which collagen fibril "shrinkage" occurs [3,26,27].…”
Section: Discussionmentioning
confidence: 97%